2014
DOI: 10.1063/1.4868388
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoscale characterization of the biomechanical properties of collagen fibrils in the sclera

Abstract: We apply the PeakForce Quantitative Nanomechanical Property Mapping (PFQNM) atomic force microscopy mode for the investigation of regional variations in the nanomechanical properties of porcine sclera. We examine variations in the collagen fibril diameter, adhesion, elastic modulus and dissipation in the posterior, equatorial and anterior regions of the sclera. The mean fibril diameter, elastic modulus and dissipation increased from the posterior to the anterior region. Collagen fibril diameter correlated line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Importantly, these phenotypes in fibronectin-null livers are accompanied by significantly elevated liver matrix stiffness, as determined by AFM, and deteriorated hepatic functions. The novel aspect of our AFM experiments is that we have simultaneously imaged the ultrastructure of the tissue and colocated the mechanical properties, using a novel AFM mechanical mapping method [ 106 ]. We have found that there is approximately a 55% increase in the elastic modulus of fibronectin-null livers compared to controls in vivo (5,128 ± 553.6 MPa in mutant versus 3,313 ± 835.2 MPa in control ( n = 9); P < 0.05; measured at ambient conditions) [ 21 ].…”
Section: Characterization Of Liver Mechanics In Vitro mentioning
confidence: 99%
“…Importantly, these phenotypes in fibronectin-null livers are accompanied by significantly elevated liver matrix stiffness, as determined by AFM, and deteriorated hepatic functions. The novel aspect of our AFM experiments is that we have simultaneously imaged the ultrastructure of the tissue and colocated the mechanical properties, using a novel AFM mechanical mapping method [ 106 ]. We have found that there is approximately a 55% increase in the elastic modulus of fibronectin-null livers compared to controls in vivo (5,128 ± 553.6 MPa in mutant versus 3,313 ± 835.2 MPa in control ( n = 9); P < 0.05; measured at ambient conditions) [ 21 ].…”
Section: Characterization Of Liver Mechanics In Vitro mentioning
confidence: 99%
“…The spring constant and deflection sensitivity was calibrated using the reference sample, and the same AFM probe was used for imaging every sample. The data were fitted with the Derjaguin-Muller-Toporov model to extract the elastic modulus, as described previously (36). For tissue samples, 10 ϫ 10-m images were collected, and the mean elastic modulus was determined using Bruker Nanoscope software, v 1.5.…”
Section: Methodsmentioning
confidence: 99%
“…PFQNM enables the co-localisation of ultrastructural and mechanical properties with a high resolution. We have previously shown that this technique allows detection of regional variations in the nanomechanical properties of collagen-rich tissue [15] . In this study, we present both nanomechanical and ultrastructural data from the adventitia in a group of patients with known low or high PWV.…”
Section: Introductionmentioning
confidence: 99%